IDENTIFICATION OF EARTHQUAKE SOURCES RESPONSIBLE FOR SUBSURFACE VLF ELECTRIC FIELD EMISSIONS OBSERVED AT AGRA - Singh V.; Kumar M.; Singh B.; Hayakawa M. (My University, 2006)
Employing USGS earthquake data for Indian region and very low frequency (VLF, 3 kHz) subsurface electric field data obtained by using a borehole antenna at Agra in India, statistical analysis has been carried out to identify the earthquake sources responsible for VLF data. The correlation coefficient between occurrence number of VLF noise bursts and earthquakes are calculated and level of hypothesis tested. The results show that seismic activities occurring close to the observing station and the main boundary fault located at the southern base of Himalaya are the main sources of VLF emissions recorded at the station. © 2006 Elsevier Ltd. All rights reserved.
Keywords: BOREHOLE ANTENNA; EARTHQUAKES; STATISTICAL ANALYSIS; VLF ELECTROMAGNETIC EMISSIONS